Detection of the Elusive Triazane Molecule (N3H5) in the Gas Phase. Issue 15 (2nd September 2015) - Förstel, Marko; Maksyutenko, Pavlo; Jones, Brant M.; Sun, Bing‐Jian; Chen, Shih‐Hua; Chang, Agnes. H.‐H.; Kaiser, Ralf I.
Abstract We report the detection of triazane (N3H5) in the gas phase. Triazane is a higher order nitrogen hydride of ammonia (NH3) and hydrazine (N2H4) of fundamental importance for the understanding of the stability of single‐bonded chains of nitrogen atoms and a potential key intermediate in hydrogen–nitrogen chemistry. The experimental results along with electronic‐structure calculations reveal that triazane presents a stable molecule with a nitrogen–nitrogen bond length that is a few picometers shorter than that of hydrazine and has a lifetime exceeding 6±2 μs at a sublimation temperature of 170 K. Triazane was synthesized through irradiation of ammonia ice with energetic electrons and was detected in the gas phase upon sublimation of the ice through soft vacuum ultraviolet (VUV) photoionization coupled with a reflectron‐time‐of‐flight mass spectrometer. Isotopic substitution experiments exploiting [D3]‐ammonia ice confirmed the identification through the detection of its fully deuterated counterpart [D5]‐triazane (N3D5).